Análise de curvas de calibração utilizadas no método do papel filtro para estimar a sucção matricial em solos não saturados - Cupertino, Kamila Furtado (2013)
Soil suction in unsaturated soils (SNS) is one of the main variables involved in the study of the hydro-mechanical behavior of these soils. There are various techniques for determining the SNS suction, and the filter paper method (MPF) is probably one of the simplest method available to estimate a wide variation in suction in unsaturated soils (30 kPa-30000 kPa). The MPF is basically the action of put the filter paper in contact, direct or indirect, with unsaturated soil sample in a closed environment, until they reach the pressure equilibrium. Equilibrium is achieved when the fluid flow ceases (matric suction) or the vapour flow ceases (suction total). Once the pressure equilibrium is reached, the suction of the soil will be the same as filter paper, and with the known relationship between the gravimetric moisture content and suction filter paper is possible to estimate the suction of the soil. This relationship is called calibration curve of the filter paper and defines the water retention curve of the filter paper. Several calibrations to the filter paper have been published in the literature and there is a significant discrepancy between them. Many of the calibrations are called bilinear (ie, two different linear equations) with an inflection point occurring between 60 kPa and 120 kPa (corresponding gravimetric moisture content values between 40 and 50%). The possibility to define a calibration curve for the filter paper Whatman No. 42 using artificial samples is evaluated in this study. The idea is to represent the best fit existing from seven previously published calibration curves the filter paper Whatman No. 42 (Fawcett and Collis-George, 1967; Hamblin, 1981; Chandler and Gutierrez, 1986; Chandler et al. 1992b; Crilly e Chandler, 1993; Leong et al., 1992; ASTM D5298-03). The variability of the calibration suggested in relation with the published seven calibrations is quantified using statistical tools. The experimental evaluation of the calibration suggested in this work, carried out by comparing the values obtained by the suction MPF and calibration suggested and results obtained with other techniques used to measure or control suction in different unsaturated soils (Fleureau et al., 2002; Soto, 2004 and Haghighi, 2011) shows that MPF with appropriate calibration curve may give satisfactory results.